Evaluation of a heating block system for accurate temperature-time controlled pasteurization treatments on various foods - Kou, Xiaoxi; Li, Rui; Hou, Lixia; Cheng, Teng; Zhou, Xu; Wang, Shaojin (International Journal of Agricultural and Biological Engineering, 2018)
For simulating real pasteurization treatments using hot air, hot water, radio frequency and microwave heating, a unique experimental heating block system (HBS) was developed. The stability and uniformity of sample temperatures and heating rates in HBS were determined for studying the thermal resistance of food-borne pathogens. A computer simulation model was also developed to analyze the behavior of thermal process in HBS. The results showed that the required heating rates with various set-temperatures and holding times could be easily and precisely achieved in eight selected food materials. Thermocouple and thermal imaging data showed that the good sample heating uniformity in six cells of HBS was achieved. The real temperature-time histories obtained by radio frequency energy could be approximately done in HBS by setting a number of linear regression curves. The HBS can help in more precisely characterizing the heat resistance of pathogens in foods to further develop pasteurization processes.Keywords: thermal treatment, heating rate, heating uniformity, thermal resistance, simulation, heating block system (HBS)DOI: 10.25165/j.ijabe.20181103.3734Citation: Kou X X, Li R, Hou L X, Cheng T, Zhou X, Wang S J. Evaluation of a heating block system for accurate temperature-time controlled pasteurization treatments on various foods. Int J Agric & Biol Eng, 2018; 11(3): 220–228.